Optoacoustic Imaging Detects Hormone-Related Physiological Changes of Breast Parenchyma - Abeyakoon, Oshaani; Morscher, Stefan; Dalhaus, Nina; Ford, Steven J.; Mendichovszky, Iosif A.; Manavaki, Roido; Wallis, Matthew; Moyle, Penelope; Woitek, Ramona; Patterson, Andrew; Torheim, Turid; Joseph, James; Gonzalez, Isabel Quiros; Bohndiek, Sarah; Gilbert, Fiona J. (Ultraschall in der Medizin - European Journal of Ultrasound, 2019)
Purpose Optoacoustic imaging with ultrasound (OPUS) can assess in-vivo perfusion/oxygenation through surrogate measures of oxy, deoxy and total hemoglobin content in tissues. The primary aim of our study was to evaluate the ability of OPUS to detect physiological changes in the breast during the menstrual cycle and to determine qualitative/quantitative metrics of normal parenchymal tissue in pre-/post-menopausal women. The secondary aim was to assess the technique’s repeatability.Materials and Methods We performed a prospective ethically approved study in volunteers using OPUS (700, 800 and 850 nm wavelengths) in the proliferative/follicular and secretory phase of the menstrual cycle. Regions of interest (ROIs) were drawn on the most superficial region of fibroglandular tissue and same-day intra-observer repeatability was assessed. We used t-tests to interrogate differences in the OPUS measurements due to hormonal changes and interclass correlation coefficients/Bland-Altman plots to evaluate the repeatability of mean ROI signal intensities.Results 22 pre-menopausal and 8 post-menopausal volunteers were recruited. 21 participants underwent repeatability examinations. OPUS intensity values were significantly higher (p < 0.0001) at all excitation wavelengths in the secretory compared to the proliferative/follicular phase. Post-menopausal volunteers showed similar optoacoustic values to the proliferative/follicular phase of pre-menopausal volunteers. The repeatability of the technique was comparable to other handheld ultrasound modalities.Conclusion OPUS detects changes in perfusion/vascularity related to the menstrual cycle and menopausal status of breast parenchyma.
Keywords: breast; hormones; physiology; optoacoustic; molecular imaging